PERAN DIT RESKRIMSUS POLDA NTB DALAM PENANGANAN PERKARA TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL (STUDI PUTUSAN PN NOMOR : 568/PID.SUS/2022/PN MTR) - MEGAYATI, DHINA (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to find out the role of the Directorate of Criminal and Criminal Investigation of the NTB Regional Police in handling cases of criminal defamation through social media (PN DECISION Study Number: 568/Pid.Sus/2022/PN Mtr), and to find out what the judge's legal considerations are in the PN decision. Number 568/Pid.Sus/2022/PN Mtr dated 7 October 2022 concerning the crime of defamation via Facebook committed by the defendant SAHBAN. This research is a type of descriptive normative legal researchIn carrying out the duties, functions and roles of the West Nusa Tenggara Regional Police Criminal Investigation Unit in handling criminal acts of defamation through social media, namely carrying out the functions and roles of carrying out investigations and investigations of special crimes in the Legal Area of the West Nusa Tenggara Regional Police. The judge's decision must provide a deterrent effect on the perpetrators of criminal acts and can make the accused become a more responsible person and be able to return to being a better member of society. The judge's decision must also be able to prevent people from committing similar criminal acts.